Development of humanized monoclonal antibody by logical approach: characterization, functional studies in vitro and immunogenicity studies in vivo in non-human primates - Cheah, S.H.; Dharshanan, S.; Chong, H.; Zamrod, Z. (Academic Journals, 2012)
Monoclonal antibodies (mAbs) are widely used due to their exquisite specificity and once were hailed as the solution to cancer. However, when mouse mAbs are administered in humans, anti-antibody response (AAR) is frequently observed. Using humanized mAbs which are commonly developed by CDR-grafting method, the AAR is negligible, but loss of binding has also been consistently reported. Therefore, in an effort to produce humanized anti-C2 mAbs that retain binding properties but produce minimal AAR, humanized mAb has been developed by logical approach using IgBLAST. The purity and functionality of humanized mAb was confirmed by Sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE) and cell-based assays, respectively. Although the humanized mAb developed using logical approach had reduced AAR compared to mouse anti-C2 mAb in Macaca fascicularis, however the AAR was higher, compared to humanized mAb developed using deimmunization method. Hence, for the development of functional humanized mAbs with negligible AAR, it is recommended that amphipathic mouse residues, excluding those located in the CDR or Vernier zone, be chosen for humanization. However, humanization of every amphipathic mouse residues is unnecessary because with minimal judicious amino acid substitutions, an AAR response can be minimized without jeopardizing the immunoreactivity, hence making it ideal for use in human therapeutics.